Management strategy and tactics - Hutchinson, John G. (New York Holt, Rinehart and Winston, inc., 1971)
Contents: Perspectives on management strategy and tactics; strategy and tactics of management; critical areas for tomorrow's managers.
Includes bibliographies.
Keywords: Quản trị kinh doanh